Synthesis, characterization and thermal behaviour of solid-state compounds of 2-methoxybenzoate with some bivalent transition metal ions - Carvalho, C.T [UNESP]; Siqueira, A. B [UNESP]; Rodrigues, E. C [UNESP]; Ionashiro, Massao [UNESP] (Editora Unesp, 2005)
compostos M-2-MeO-Bz foram sintetizados no estado sólido, onde M representa os íons bivalentes Mn, Co, Ni, Cu e Zn e 2-MeO-Bz é o anion 2-metoxibenzoato. Esses compostos foram caracterizados e estudados, utilizando-se técnicas de difração de raios X pelo método do pó, espectroscopia na região do infravermelho, complexometria e analise térmica diferencial simultânea (TG-DTA), thermogravimetry, derivative thermogravimetry (TG/DTG) e calorimetria exploratória diferencial (DSC). Os resultados permitiram obter informações com respeito a estequiometria, desidratação, estabilidade térmica e decomposição térmica.

Solid-state M-2-MeO-Bz compounds, where M stands for bivalent Mn, Co, Ni, Cu and Zn and 2-MeO-Bz is 2-methoxybenzoate, have been synthesized. Simultaneous thermogravimetry-differential thermal analysis (TG-DTA), thermogravimetry, derivative thermogravimetry (TG/DTG), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results led to have information about the composition, dehydration, thermal stability and thermal decomposition of the isolated compounds.
Síntese, caracterização e comportamento térmico dos 2-metoxibenzoatos de alguns íons metálicos bivalentes de transição, no estado sólido
Keywords: metais de transição bivalente; 2-metoxibenzoato; comportamento térmico; bivalent transition metals; 2-methoxybenzoate; thermal behaviour